Pengembangan E-Bahan Ajar Berbasis SETS (Science, Environment, Technology and Society) Terintegrasi Potensi Lokal pada Pendidikan Lingkungan Hidup - Erika Fitri Wardani; Diah Rina Miftakhi (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to develop SETS-based e-teaching materials (Science, Environment, Technology, Society) that integrates the local potential of Bangka Belitung in Environmental Education courses. The method used in this research is the ADDIE development model, which consists of 5 stages, including analysis, design, development, implementation and evaluation. The results showed that the average percentage data from each expert validation were: 1) media experts obtained an average of 93.75% with validity criteria (very valid) and eligibility criteria (very feasible); 2) the average of material experts is 95.45% with validity criteria (very valid) and eligibility criteria (very feasible); 3) the average of linguists is 91.66% with validity criteria (very valid) and eligibility criteria (very feasible); 4) the results of the limited trial obtained an average of 95.62% with the criteria of validity (very valid) and eligibility criteria (very feasible). In conclusion, e-teaching materials have met the validity and eligibility to be used in the learning process of Environmental Education. Keywords: SETS-Based Teaching Materials, Local Potential of Bangka Belitung